2006
DOI: 10.1038/sj.ki.5001649
|View full text |Cite
|
Sign up to set email alerts
|

Role of P-glycoprotein in cyclosporine cytotoxicity in the cyclosporine–sirolimus interaction

Abstract: Cyclosporine nephrotoxicity remains a major side effect in solid organ transplantation, and can be exacerbated by concomitant administration of sirolimus. Cyclosporine and sirolimus are P-glycoprotein (Pgp) substrates. We hypothesized that the Pgp activity level may affect cyclosporine cytotoxicity by interfering with the ability of Pgp to remove cyclosporine from within tubular cells, and that an interaction between cyclosporine and sirolimus on Pgp function may explain the enhancement of cyclosporine nephrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 37 publications
1
56
0
1
Order By: Relevance
“…21 This enhanced renal tissue exposure when both drugs are combined appears to be mediated by P-glycoprotein (P-gp) inhibition in renal tubular cells. 46 In an in vitro human epithelial renal cell model, Anglicheau and associates 46 demonstrated that rapamycin exerted an inhibitory effect on P-gp and increased intracellular cyclosporine concen-trations and cell death in a dose-dependent manner. The P-gp efflux pump, an ABCB1 (previously multidrug resistance 1) gene product, is a membrane protein that functions as an ATP-dependent exporter.…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…21 This enhanced renal tissue exposure when both drugs are combined appears to be mediated by P-glycoprotein (P-gp) inhibition in renal tubular cells. 46 In an in vitro human epithelial renal cell model, Anglicheau and associates 46 demonstrated that rapamycin exerted an inhibitory effect on P-gp and increased intracellular cyclosporine concen-trations and cell death in a dose-dependent manner. The P-gp efflux pump, an ABCB1 (previously multidrug resistance 1) gene product, is a membrane protein that functions as an ATP-dependent exporter.…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
“…These histologic findings have been reported to be associated with mTOR inhibitor monotherapy or in combination therapy with CNI and at therapeutic concentrations, in both animal and human models. 7,11,[16][17][18][21][22][23]46,47 In fact, Piao and associates 47 recently demonstrated, using an in vivo experimental animal model, that combined treatment with cyclosporine and the mTOR inhibitors (rapamycin and everolimus) significantly increased cyclosporine or mTOR inhibitor concentrations in kidney tissue versus treatment with cyclosporine or mTOR inhibitor alone, despite similar whole blood levels of either drug. This increase in tissue concentration of both drugs was associated with an exaggeration in oxidative stress and an aggravation in renal injury with significant deterioration in renal function in the combination therapy group versus with monotherapy.…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
“…A characteristic cast nephropathy lesion has also been reported with use of mTOR inhibitors. [53][54][55] Renal Sparing Strategies…”
Section: Kidney Injury and Immunosuppressionmentioning
confidence: 99%
“…First, there is the observation that both sirolimus and everolimus increase chronic nephrotoxicity of CNIs, both in rats (272) and in humans (273)(274)(275). This is explained by robust evidence that these mTOR inhibitors interact with cyclosporine excretion in tubular epithelial cells through competition for P-glycoprotein (276,277), and hence lead to accumulation of cyclosporine in these cells. Local renal accumulation of cyclosporine was demonstrated in vitro by Anglicheau et al (277) and in vivo by Napoli et al (278) and Podder et al (279).…”
Section: Local Renal Exposure To Cyclosporine and Tacrolimusmentioning
confidence: 99%
“…This is explained by robust evidence that these mTOR inhibitors interact with cyclosporine excretion in tubular epithelial cells through competition for P-glycoprotein (276,277), and hence lead to accumulation of cyclosporine in these cells. Local renal accumulation of cyclosporine was demonstrated in vitro by Anglicheau et al (277) and in vivo by Napoli et al (278) and Podder et al (279). These latter studies measured increased local renal cyclosporine concentrations in kidney tissue after concomitant treatment with sirolimus in rats.…”
Section: Local Renal Exposure To Cyclosporine and Tacrolimusmentioning
confidence: 99%